2015
DOI: 10.1002/asia.201501048
|View full text |Cite
|
Sign up to set email alerts
|

Aquation Is a Crucial Activation Step for Anticancer Action of Ruthenium(II) Polypyridyl Complexes to Trigger Cancer Cell Apoptosis

Abstract: Aquation has been proposed as crucial chemical action step for ruthenium (Ru) complexes, but its effects on the action mechanisms remain elusive. Herein, we have demonstrated the aquation process of a potent Ru polypyridyl complex (RuBmp=[Ru(II) (bmbp)(phen)Cl]ClO4 , bmbp=2,6-bis(6-methylbenzimidazol-2-yl) pyridine, phen=phenanthroline) with a chloride ligand, and revealed that aquation of RuBmp effectively enhanced its hydrophilicity and cellular uptake, thus significantly increasing its anticancer efficacy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 59 publications
2
7
0
Order By: Relevance
“…4A, phosphorylation of MAPKs was activated in Ru2-induced apoptotic pathways, and there was no significant change in phosphorylation of AKT. Notably, Ru2 treatment up-regulated the phosphorylation level of ERK (p-ERK) dramatically, which was not in accordance with previous reported of ruthenium complexes [8][9][10]. Moreover, the level of p-ERK increased in a time-dependent manner (Fig.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…4A, phosphorylation of MAPKs was activated in Ru2-induced apoptotic pathways, and there was no significant change in phosphorylation of AKT. Notably, Ru2 treatment up-regulated the phosphorylation level of ERK (p-ERK) dramatically, which was not in accordance with previous reported of ruthenium complexes [8][9][10]. Moreover, the level of p-ERK increased in a time-dependent manner (Fig.…”
supporting
confidence: 69%
“…Although many studies on the abilities of Ru(II) polypyridyl complexes to modulate the ERK signaling pathways have been reported [8][9][10], data on the effect of these complexes on ERK activation and subsequent cellular responses remain limited. Hence, in this study, two compounds containing 2,2-bipyridine (bpy) ligands with 3-(pyrazin-2-yl)- [1,2,4] triazino [5,6-f] [1,10]phenanthroline (pztp) or 3-(pyridin-2-yl)- [1,2,4] triazino [5,6-f] [1,10]phenanthroline (pytp) as main ligands; Ru1 and Ru2 (Fig.…”
mentioning
confidence: 98%
“…Several studies supported our results of the apoptotic activation of ruthenium compounds on different cell lines. [ 101,102 ] However, the ruthenium compounds may have another way to destroy cancer cell besides apoptosis but needs more analysis to be confirmed which will be discussed in our future in vivo study.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…3 ). The activation of caspase-9 suggested the induction of the mitochondria-mediated apoptotic pathway, while the activation of caspase-8 indicated the induction of death receptor-mediated apoptosis ( 29 ). These results revealed that bufotalin induces ESCC cell apoptosis through the activation of caspase-mediated apoptosis, with the involvement of mitochondria and death receptors.…”
Section: Resultsmentioning
confidence: 99%